Performance of prostate health index and PSA density in a diverse biopsy‐naïve cohort with mpMRI for detecting significant prostate cancer. Issue 6 (15th June 2021) - Carbunaru, Samuel; Stinson, James; Babajide, Rilwan; Hollowell, Courtney M. P.; Yang, Ximing; Sekosan, Marin; Ferrer, Karen; Kajdacsy‐Balla, Andre; Abelleira, Josephine; Ruden, Maria; King‐Lee, Patrice; Dalton, Daniel P.; et al.
Abstract: Objective: To compare Prostate Health Index (PHI) and prostate‐specific antigen (PSA) density as secondary tests after multiparametric magnetic resonance imaging (mpMRI) in improving the detection accuracy of Gleason grade group (GG) 2‐5 prostate cancer (PCa) and in decreasing unnecessary biopsies in a multiethnic biopsy‐naïve population. Methods: From February 2017 to February 2020, we recruited consecutive biopsy‐naïve men in participating urology clinics for elevated PSA levels. They all had a PHI score, mpMRI, and prostate biopsy. Experienced genitourinary radiologists read all mpMRI studies based on PIRADS version 2.0. Logistic regression models were used to generate receiver operating characteristic curves. Models were tested for effect modification between Race (Black vs White) and both PHI and PSA density, and Race and PIRADS to determine if race impacted their prediction accuracy. Sensitivity, specificity, and predictive values of PHI and PSA density thresholds were calculated by PIRADS scores. The primary outcome was GG2‐5 PCa, that is, Gleason score ≥3 + 4. Results: The study included 143 men, of which 65 (45.5%) were self‐reported Black. Median age was 62.0 years and 55 men (38.4%) had GG2‐5 PCa. Overall, 18.1% had PIRADS 1‐2, 32.9% had PIRADS 3, and 49.0% had PIRADS 4‐5. For the binary logistic regressions, the interactions between PIRADS and Race ( P = .08), Log (PHI) and Race ( P = .17), and Log (PSA density) and Race ( P = .42) were not statistically significant. Within PIRADS 3 lesions, a PHI ≥49 prevented unnecessary biopsies in 55% of men and missed no GG2‐5 PCa, yielding a negative predictive value of 100%. There was no reliable PHI or PSA density threshold to avoid PCa biopsies in PIRADS 1‐2 or 4‐5. Conclusions: PHI and PSA density can be used after mpMRI to improve the detection of GG2‐5 PCa in a biopsy‐naïve cohort. PHI may be superior to PSA density in PIRADS 3 lesions by avoiding 55% of unnecessary biopsies. Using both PHI and PSA density in series may further increase specificity and lead to fewer unnecessary biopsies, but further larger studies are warranted to determine the optimal threshold of each biomarker.